IMPLEMENTATION OF ACCELEROMETER SENSOR AND GPS MODULE FOR SMART BIKE DESIGN - Faisal Alfaeru; Aries Boedi Setiawan; Nachrowi Nachrowi; Rachmat Hidayat S Hidayat S (International Conferences SDGs 2030 Challenges and Solutions, 2030)
Bicycles are one vehicle that is quite popular for exercise. The lack of parking space for bicycles made bicycles vulnerable to theft. This equipment is able to provide a security system and provide the location of the bike when the bike had been stolen. This device consists of an Android application and the application of two modules, namely accelerometer and GPS to be processed in the microcontroller Arduino UNO. This bike is able to provide information such as SMS when the bicycle displaced and also sends the coordinates of the location on google maps to be displayed to the smartphone applications created using MIT App Inventor 2.